Banking Crises - Richard S. Grossman (Center for Economic Studies and ifo Institute (CESifo), 2016)
Financial crises have been a common feature of the economic landscape for more than two centuries. The chapter defines banking crises, considers the type of costs that they impose, and outlines the most common causes of banking crises during the past 200 years. The remainder of the chapter considers five distinct historical periods: the nineteenth century, when the “boom-bust” pattern that would typify later crises became established; the inter-war period, which was punctuated by two major sets of crises (post-World War I crisis and the Great Depression); the post-World War II financial lock-down, which was characterized by a complete absence of banking crises; deregulation and the return of crises in the 1970s; and the subprime crisis that emerged in 2008 and the subsequent euro-zone crisis.
Keywords: 330; banking crises